Sistem Informasi Pengenalan Hewan Berbasis Multimedia Interaktif - Andi Soehartanto Putra; Firma Mukarromah; Usama Waliyyudin; Hersa Dwi Ikhsanti; Fatwa Meilidya; TB. Ahmad Fadhlan Shaquille (Program Studi Pendidikan Informatika, Universitas Citra Bangsa, 2023)
Information technology is developing very rapidly, thus making the use of information technology also growing. However, there are still many problems found by teachers in teaching and learning activities with conventional methods. For example, in the learning process, children often joke with their friends or have fun with their toys. The purpose of this study is to find solutions to these problems, either solution is with multimedia system-based learning. Creating an animation using macromedia flash 8 software can attract children's interest to learn about various animals, sounds and shapes so that learning is fun so it can be understood well and not boring. This research produces animation-based learning media that is very useful for teachers as an interesting alternative tool when providing learning material, so that this material can be understood well by children.